Impact of Social Networking Tools on Undergraduate Students (Science Stream): An Analytical Study - Gupta, Ekta; Gulati, Anjali (Journal of Information and Knowledge, 2021)
Social Networking Sites (SNSs) have transformed the world by connecting people more than ever before. The present study seeks to examine the impact of social media on the overall development of undergraduate students enrolled in a reputed degree college based on a sample 112 students. Questionnaire method was used to collect data on the perceived usefulness and effectiveness of social networking tools among undergraduate science students. The study has also examined how social networking sites have influenced the academic and professional development of students. Additionally, the study has demonstrated the extent of involvement of students in the activities on SNSs and their purpose behind using SNSs. The researcher found these sites to be helpful for the students in improving their academic performance, preparing them for competitive exams, increasing their learning and research capabilities, and enhancing information technology skills.